Blue's clues & you. Let's learn with Blue [videorecording (DVD)] (Paramount, 2022)
Practice letter recognition and sounds as Josh, Blue, and their friends learn all about ABCs. Next, it's 123s as we count along and help Josh discover what he can buy with Blue dollars. Then, learn about science as we meet the Sun, study the world through a magnifying glass, and sing a song about the planets! Also, Josh and Blue Skidoo to help finish a painting and so much more!